Differential Myocardial Responses in Male and Female Rats with Uremic Cardiomyopathy - Bódi Beáta; Vágó Rebeka Rita; Nagy László; Ráduly Arnold Péter; Gulyás András; Kupecz Klaudia; Azar Lilian; Márványkövi Fanni Magdolna; Szűcs Gergő; Siska Andrea; Cserni Gábor; Földesi Imre; et al. (2025)
Uremic cardiomyopathy, characterized by diastolic dysfunction, left ventricular hypertrophy (LVH), and fibrosis, is a common cardiovascular complication of chronic kidney disease (CKD). Men are at a higher risk for cardiovascular and renal diseases, compared to age-matched, pre-menopausal women. We aimed to investigate the influence of sex on the severity of uremic cardiomyopathy through the characterization of functional and molecular indices of myocardial remodeling in a rat model. CKD was induced by a 5/6 nephrectomy in 9-week-old male and female Wistar rats. Serum and urine tests, transthoracic echocardiography, left ventricular (LV) histology, and quantitative reverse transcription polymerase chain reaction (RT-qPCR) were performed at week 8 or 9. Moreover, LV alterations were also tested in permeabilized cardiomyocytes (CMs) by force measurements and Western immunoblotting. CKD resulted in the development of a more severe uremic cardiomyopathy in male rats—including LVH, LV diastolic dysfunction, and fibrosis—than in female rats, where only LVH was observed. A uremic cardiomyopathy was also associated with a decrease in maximal Ca2+-activated force (Fmax) in CMs of male rats. Additionally, increases in CM Ca2+-independent passive stiffness (Fpassive) and decreases in cardiac myosin-binding protein C (cMyBP-C) phosphorylation levels were significantly larger in male than female rats. In conclusion, a uremic cardiomyopathy involved cardiac remodeling in both sexes. Nevertheless, male rats exhibited more pronounced signs of macroscopic and microscopic alterations than their female counterparts, illustrating a sex-dependent component of uremic cardiomyopathy.
Keywords: Klinikai orvostan